2017
DOI: 10.1016/j.rser.2016.11.227
|View full text |Cite
|
Sign up to set email alerts
|

Energy consumption in the US reconsidered. Evidence across sources and economic sectors

Abstract: This study analyzes the impact of GDP shocks in USA on primary energy consumption and the reverse impact in a comprehensive and novel framework, distinguishing by economic sectors (commercial, industrial, residential and transportation) and energy source, i.e., total fossil (coal, natural gas and petroleum), nuclear, and renewable (hydroelectric, geothermal and biomass) for the period 1973:1 to 2015:2. To this end, we apply Granger causality analysis through the Hatemi-J [1] and Toda and Yamamoto [2] approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The adverse effect of utilizing energy derived from fossil sources like coal and crude oil on the environment has propelled the quest for a more sustainable, renewable, and cleaner form of energy. 1,2 Based on the latest emission gap report of the United Nations Committee on climate change, greenhouse gas emissions need to be cut globally by 7.6% every year for the next decade to comply with the Paris target. 3 However, it is worrisome to know that the global greenhouse gases (GHG) emissions are on the increase.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effect of utilizing energy derived from fossil sources like coal and crude oil on the environment has propelled the quest for a more sustainable, renewable, and cleaner form of energy. 1,2 Based on the latest emission gap report of the United Nations Committee on climate change, greenhouse gas emissions need to be cut globally by 7.6% every year for the next decade to comply with the Paris target. 3 However, it is worrisome to know that the global greenhouse gases (GHG) emissions are on the increase.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers analyzed the impact of energy structure, technological progress, and industrial structure on energy intensity with the logarithmic mean Divisia index technique, the results show that energy structure and industrial structure have different effects on energy intensity [15][16][17]. Cross-correlations between energy structure and industrial structure based on the well-known detrended cross-correlation analysis are shown to be significant and strong [18,19]. Some authors described the historical evolution of various end uses in the different energy sectors through mapping Sankey diagrams.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Baumol's (1986) view is particularly useful as it explores in a simple and straightforward manner assumptions tacitly embraced not only by neoclassical economists, but also by the economic order triggered by the Industrial Revolution. Although Baumol's model (1986) was published more than 30 years ago, it remains an important reference to address neoclassical thinking about the relation between natural resources, economic growth and technological innovation (Earp & Romeiro, 2015;Kalimeris et al, 2014;Chen et al, 2017;Carmona et al, 2017;Bithas & Kalimeris, 2016). Moreover, the premise that there are almost no limits for scientific/technological progress to increase efficiency in the use of natural resources has been endorsed in the core of the neoclassical mainstream of environmental economics (Romeiro, 2012, p. 73).…”
Section: Introductionmentioning
confidence: 99%